Innovative Development of Batch Dyed 3D Printed Acrylonitrile/Butadiene/Styrene Objects - Suzana Kutnjak-Mravlinčić (MDPI AG, 2021)
According to the great impact of additive technology on the development of modern industry, a lot of research is being done to obtain 3D printed parts with better properties. This research is extremely important because there are no scientific papers in the field of post dyeing of acrylonitrile/butadiene/styrene (ABS) 3D printed parts. The experiment was carried out using disperse dyes on ABS specimens. The obtained coloration of the specimens was in the primary colors (yellow, red, and blue) in the specified dyestuff concentration range and was evaluated using an objective CIELab system. Based on the obtained color parameters, remission values and Kubelka-Munk coefficient, dye mixtures and an ombre effect were performed to obtain patterns in the desired hues. Abrasion resistance of disperse dyed specimens was tested using different abrasive materials over a wide range of fineness to simulate different indoor and outdoor soils and was compared to abrasion resistance of specimens produced from the industrially dyed wire with the master batch. The results show that 3D printed ABS products can be produced in one or more desired shades with satisfactory abrasion resistance. This undoubtedly represents the added value of 3D printed ABS parts and extends their application to the field of creative industries and design, specifically footwear design.